Examining Primary Care Physicians' Intention to Perform Cervical Cancer Screening Services Using a Theory of Planned Behavior: A Structural Equation Modeling Approach - Hu, Zhiqing; Sun, Yanjun; Ma, Yuhao; Chen, Kejin; Lv, Ling; Wang, Lingling; He, Yuan (Frontiers in Public Health, 2022)
Background: The promotion of cervical cancer screening (CCS) is undoubtedly effective in tackling the serious public health problem in developing country, but its implementation faces some challenges. Understanding the influencing factors of primary care physicians’ intention to provide cervical cancer screening services (CCSs) for rural women is crucial for future implementation of screening program. The aim of our study was to assess primary care physicians’ intention to provide CCSs for rural women and the determinants of it. Methods: In this cross-sectional study, 1308 primary care physicians in rural primary health care participated, the data collection tool was designed based on the theory of planned behavior, which included demographic characteristics, basic constructs of TPB and the knowledge level regarding CCSs as the extended variable of TPB model. Structural equation modeling was used to analysis the relationships of each factor. Results: Pathway analysis found that TPB is a suitable theoretical basis to predict the primary care physicians’ intention to provide CCSs :(χ2/df=2.297, RMSEA=0.034, SRMR=0.039). The model predicted 39% of the variation in primary care physicians’ intention to provide CCSs. Meanwhile, the structural equation model showed that attitude (β=0.265, p<0.001), subjective norm (β=0.311, p<0.001), perceived behavior control (β=0.163, p<0.001) and knowledge level (β=0.153, p< 0.01) could positively predict primary care physicians’ intention to provide CCSs. Conclusions: TPB model with addition of knowledge was useful for predicting primary care physicians’ intention to provide CCSs for Chinese rural women. Findings of our study offer a reference for government and hospitals to make the strategies of improving the primary care physicians’ intention to provide CCSs.